Optical effects on the surrounding structure during quantitative analysis using indocyanine green videoangiography: A phantom vessel study. Issue 4 (3rd January 2018) - Tsukiyama, Atsushi; Murai, Yasuo; Matano, Fumihiro; Shirokane, Kazutaka; Morita, Akio
Abstract : Various reports have been published regarding quantitative evaluations of intraoperative fluorescent intensity studies using indocyanine green (ICG) with videoangiography (VAG). The effects of scattering and point‐spread functions (PSF) on quantitative ICG‐VAG evaluations have not been investigated. Clinically, when ICG is administered through the peripheral vein, it reaches the tissue intra‐arterially. To achieve more reliable intraoperative quantitative intensity evaluations, we examined the impact of high‐intensity structures on close areas. The study was conducted using a phantom model and surgical fluorescent microscope. A region of interest (ROI) was created for the vessel model and another ROI was created within 3 cm of that. With an ROI of 6.8 mm in the vessel phantom model, 10% intensity was confirmed, even though there was no fluorescent structure. Intensity decreased gradually as the ROI moved further from the vessel model. Our study results suggest that the presence of a high‐intensity structure and the size of the ROI may affect quantitative intensity evaluations using ICG‐VAG. Results of linear regression analysis indicate that the relationship of intensity ( Y ) and distance ( X ) is as follows: Y (real/ A ) = 29 Exp(−0.062 X ) + 164.3 Exp(−1.81 X ). The optical effect should be considered when performing an intraoperative intensity study with a surgical microscope. Abstract : Basic research on cerebral blood flow (CBF) evaluation using intraoperative fluorescence test is reported. Recently, clinical CBF evaluation using indocyanine green (ICG) was performed, but quantitative evaluation using luminance is rare. When ICG is administered to the peripheral vein, it flows into the cerebral artery. However, ICG becomes highly concentrated in the artery. The resulting effect on luminance evaluation of the brain cortex was investigated.